Análisis de la incidencia de la pandemia Covid-19 en las mipymes de la provincia de El Oro. - Salvador Guevara, Pamela Dayana; Cruz Acosta, Jeiner Josue (Machala : Universidad Técnica de Machala, 2022)
The objective of this degree work was to analyze the incidence of the effects caused by the Covid-19 pandemic in micro, small and medium enterprises belonging to the Province of El Oro. Therefore, it was based on the explanation of the importance of MSMEs in the Ecuadorian economy and how the crisis affected the business structure. The methodology used for the development of the research was of the documentary and field type; in addition, the deductive and historical-comparative methods were used together with the survey as a research technique, which according to the sample was directed to 381 MSMEs in the province of El Oro. From the results it was observed that the MSMEs faced a series of problems caused by the pandemic and therefore applied certain strategies and support measures to cope with them. In conclusion, Covid-19 has had a strong impact on MSMEs in the province of El Oro causing economic and social instability effects due to the vulnerability of this group of companies that were forced to make decisions to face this negative impact on their productive activities.
El presente trabajo de titulación tuvo como objetivo analizar la incidencia de los efectos provocados por la pandemia Covid-19 en las micro, pequeñas y medianas empresas pertenecientes a la Provincia de El Oro. Por lo tanto, se basó en la explicación de la importancia de las Mipymes en la economía ecuatoriana y cómo la crisis afectó a la estructura empresarial. La metodología empleada para el desarrollo de la investigación fue de tipo documental y de campo; además, se utilizaron los métodos deductivo e histórico-lógico junto con la encuesta como técnica de investigación, la cual según la muestra fue dirigida a 381 Mipymes de la provincia de El Oro. A partir de los resultados se observó que las Mipymes se enfrentaron a una serie de problemas ocasionados por la pandemia por lo que aplicaron ciertas estrategias y medidas de apoyo para sobrellevarlos. En conclusión, la Covid-19 ha incidido fuertemente en las Mipymes de la provincia de El Oro provocando efectos de inestabilidad económica y social ante la vulnerabilidad de este grupo de empresas que fueron obligadas a tomar decisiones para enfrentar este impacto negativo en sus actividades productivas.
Keywords: MIPYMES; COVID-19; MEDIDAS DE APOYO; ESTRATEGIAS EMPRESARIALES